Acyclic cucurbit[n]uril bearing alkyl sulfate ionic groups - Christian Akakpo; Peter Y. Zavalij; Lyle Isaacs (Beilstein Journal of Organic Chemistry)
We report the synthesis and characterization of a new acyclic cucurbit[n]uril (CB[n]) host C1 that features four alkyl sulfate ionic groups. The X-ray crystal structure of the C1·Me6CHDA complex is reported. Host C1 is significantly less soluble in water (4 mM) compared to the analogous acyclic CB[n] host M1 which features sulfonate ionic groups (346 mM). Host C1 does not undergo significant self-association according to the results of 1H NMR dilution experiments. The molecular recognition behavior of the hosts C1 and M1 toward a panel of seven ammonium ions was explored by 1H NMR spectroscopy and isothermal titration calorimetry (ITC). We find that C1 generally binds slightly more tightly than M1 toward a specific guest. C1 binds more tightly to quaternary ammonium guests compared to the corresponding primary ammonium ions.